ABOUT PERSIAN LEXEMS RELATING TO THE ADJECTIVE CATEGORY IN THE EPIC "SADDI ISKANDARIY" (Scientific journal of the Fergana State University, 2025)
This article discusses the Persian adjectives used in Alisher Navoi's epic poem "Saddi Iskandariy". The work presents information on the etymological features of Persian lexemes related to the adjective category, their lexical meanings, their basis in Persian-Tajik explanatory dictionaries, comparison with explanations in other sources, and explanations of Persian adjectives in the explanatory dictionary of Navoi's works. The main goal of the article is to analyze Persian lexemes related to the adjective category. The article also discusses the synonyms of the Persian adjectives mentioned in the article, as well as adjectives formed from the noun category.